(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
The essay makes a chronological recognition of mediation in Roman law: starting with the prevailing role of the negotiating formalism in the archaic age we then find, in the classical age, different figures of mediators, and then arrive, in the postclassical and Justinian age, to the creation of a system of rules for drafting documents. Each of these ages is characterized by a different balance between the will of the parties, the function of mediation and the intervention of witnesses.